FACTOR DETERMINATION ANALYSIS OF FARMER'S ASSETS AFTER THE TSUNAMI IN ACEH - Adhiana, Adhiana; Suryadi, Suryadi (Universitas Brawijaya, Indonesia, 2017)
Limitations of access and loss of various life assets caused by tsunami and conflicts in Aceh faced by farmers have influenced their survival. The purpose of this research is to analyze the model of factor determination of farmer's assets after the-tsunami in Aceh. This study was conducted in Aceh Province covering five areas: Aceh Barat, Aceh Besar, Pidie Jaya, Bireun and Aceh Utara. The total sample for this study was 280 farmers. Sampling method used is stratified random sampling method. This research used primary data obtained by survey using questionnaire and secondary data. Data was analyzed by using qualitative and quantitative method with Structural Equation Modeling model is by measurement model. Model 2 is used as the final model for the construct of the farmer's living assets as it demonstrates good model compatibility. It also indicates that all loading factor values are above 0.5 and all probability values are significant at a = 1%. It indicated that all indicators can explain the existing constructs.